Pronunciation Problems of English Segmental Sounds Encountered by EFL Learners of English Education Study Program - Yulianti, Lola Dwi; Marhum, Mochtar; Kamaruddin, Abdul (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
The challenge of mastering English pronunciation poses significant problems for Indonesian students, who are accustomed to their native language. The English Education Study Program aims to cultivate proficient English speakers; however, many learners struggle with pronunciation despite this goal. This research aims to investigate the pronunciation problems encountered by EFL learners and to find out the underlying factors affecting the problems. Utilizing a descriptive qualitative approach, the research involved 20 participants of third-semester English Education Study Program. Data were gathered through pronunciation tests, questionnaires, and interviews. The findings reveal that the primary pronunciation problems lie in segmental features, particularly with fricative consonant sounds /v/, /ð/, /ʒ/, /θ/, and /z/, as well as vowel sounds /æ/, /ɔ:/, /ɜ:/, /u:/, and /ɑː/. These problems predominantly arise from the absence of similar sounds in Indonesian, leading to systematic substitutions with more familiar phonemes. Additionally, inconsistencies in English phonetics and the divergence between written and spoken forms exacerbate these problems. The research identifies four main factors affecting pronunciation problems: (1) the influence of native language, (2) age, (3) amount of exposure to English, and (4) phonetic coding ability. The implication of this research suggest that instructors incorporate phonetics training into their curriculum to aid students in improving their pronunciation skills.